2012
DOI: 10.1002/art.33447
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of new bone formation in patients with ankylosing spondylitis and patients with diffuse idiopathic skeletal hyperostosis: A retrospective cohort study over six years

Abstract: Objective. Ankylosing spondylitis (AS) and diffuse idiopathic skeletal hyperostosis (DISH) are both characterized by new bone formation in the spine but presumably have a different pathogenesis. This study was undertaken to compare the natural course of new bone formation in AS and DISH.Methods. Lateral radiographs of the cervical and lumbar spine from AS and DISH patients obtained at >2 time points within 6 years were analyzed to quantify osteophyte development. Radiographs were scored in a blinded manner by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 39 publications
2
24
0
1
Order By: Relevance
“…[37][38][39] These modalities are also helpful in the evaluation of peripheral enthesopathy for which US is also a readily available and sensitive tool. 40 A small case-control study suggested that MRI was capable to detect vertebral corner fat infiltration similar to findings in AS.…”
Section: Imaging Characteristicsmentioning
confidence: 99%
“…[37][38][39] These modalities are also helpful in the evaluation of peripheral enthesopathy for which US is also a readily available and sensitive tool. 40 A small case-control study suggested that MRI was capable to detect vertebral corner fat infiltration similar to findings in AS.…”
Section: Imaging Characteristicsmentioning
confidence: 99%
“…In ax-SpA, there is some evidence that inflammation precedes radiographic progression in the skeleton (36,37) or that new bone formation can be considered as a repair mechanism associated with the transformation of new inflammatory lesions to fatty degenerative changes (38,39). However, formation of enthesophytes can occur in absence of inflammation and may be due to excess of mechanical stress and composition of the bone matrix.…”
Section: Prevalence Of Structural Lesions and Mechanisms Of Formationmentioning
confidence: 99%
“…Establishing the presence of DISH in patients with SpA can be useful in better evaluating the damage to the musculoskeletal system and the cardiovascular risk. It is desirable that interest in DISH continue to expand because an understanding of the mechanisms involved in the bone proliferation of DISH could also elucidate the relationships between inflammation and bone proliferation in axial and peripheral SpA 21 .…”
Section: Rheumatologymentioning
confidence: 99%